Systematic investigation of sequence and structural motifs that recognize ATP. (June 2015) - Chen, Ke; Wang, Dacheng; Kurgan, Lukasz
Graphical abstract: (A) Superimposed cluster of ATP-binding site structures that belong to the "class II aminoacyl- tRNA synthetase" binding mode. (B) Structural motif identified by a clustering method for the "class II aminoacyl- tRNA synthetase" binding mode. Highlights: Five ATP–protein interaction binding modes are discovered. Sequence motifs are refined for two known motifs and identified for three novel motifs. A method is developed to identify structurally conserved residues and structural motifs. Abstract: Interaction between ATP, a multifunctional and ubiquitous nucleotide, and proteins initializes phosphorylation, polypeptide synthesis and ATP hydrolysis which supplies energy for metabolism. However, current knowledge concerning the mechanisms through which ATP is recognized by proteins is incomplete, scattered, and inaccurate. We systemically investigate sequence and structural motifs of proteins that recognize ATP. We identified three novel motifs and refined the known p -loop and class II aminoacyl-tRNA synthetase motifs. The five motifs define five distinct ATP–protein interaction modes which concern over 5% of known protein structures. We demonstrate that although these motifs share a common GXG tripeptide they recognize ATP through different functional groups. The p -loop motif recognizes ATP through phosphates, class II aminoacyl-tRNA synthetase motif targets adenosine and the other three motifs recognize both phosphates and adenosine. We show that some motifs are shared by different enzyme types. Statistical tests demonstrate that the five sequence motifs are significantly associated with the nucleotide binding proteins. Large-scale test on PDB reveals that about 98% of proteins that include one of the structural motifs are confirmed to bind ATP.